Temporal trends in anxiety and depression prevalence and their association with adverse outcomes in patients hospitalized for acute exacerbations of chronic obstructive pulmonary disease in Beijing, China, from 2004 to 2020 - Feng, Lin; Li, Jiachen; Lv, Xiaoshuang; Chu, Shuilian; Li, Changwei; Zhang, Ruiyuan; Cao, Xi; Liang, Lirong (Frontiers in Psychiatry, 2022)
Aims: To investigate the temporal trend in anxiety and/or depression prevalence in patients hospitalized for acute exacerbation of chronic obstructive pulmonary disease (AECOPD) in Beijing and their association with adverse outcomes. Methods: Hospital admission records from 2004 to 2020 with a primary discharge diagnosis of AECOPD were retrieved from Beijing Public Health Information Centre database. The anxiety and depression were identified from discharge diagnoses of each record. Joinpoint regression was used to analyze the temporal trend and calculate the annual percentage change (APC) for the prevalence of anxiety and/or depression. Generalized linear model was used to analyze the associations between anxiety and/or depression and patients’ adverse outcomes. Results: A total of 382,125 records were included, most of which were male (66.0%) and aged ≥75 years (59.7%). Three segments in the temporal trend were observed, with a mild increase during 2004 to 2009 (APC: 5.9%, 95% CI: -14.9 to 31.7%), followed by a sharply increase during 2009 to 2012 (APC: 60.4%, 95% CI: 10.6 to 132.7%), then stabilized at about 3% during 2012 to 2020 (APC: 1.9%, 95% CI: -0.4 to 4.3%). On average, anxiety and/or depression was more prevalent in females, the aged and those admitted in secondary hospitals (all P <0.001). Patients with anxiety and/or depression had lower in-hospital mortality (OR=0.74, 95% CI: 0.63 to 0.88), but longer hospital stay (OR=1.10, 95% CI: 1.07 to 1.13), more medical costs (OR=1.12, 95% CI: 1.08 to 1.17) and higher risks of readmission for AECOPD at 30-day, 90-day, 180-day and 1-year (ORs ranged from 1.22 to 1.51). Conclusions: The prevalence of anxiety and/or depression in patients hospitalized for AECOPD in Beijing stabilized at approximately 3% after 2012. Anxiety and/or depression is associated with a heavier burden on patients, health care and medical insurance systems. Appropriate diagnosis and effective treatment of anxiety and depression is crucial for patients with AECOPD.